2016
DOI: 10.1364/ao.56.000b64
|View full text |Cite
|
Sign up to set email alerts
|

Intermixing studies in GaN_1−xSb_x highly mismatched alloys

Abstract: GaN1−xSbx with x~ 5-7% is a highly mismatched alloy predicted to have favorable properties for application as an electrode in a photo-electrochemical cell for solar water splitting. In this study, we grew GaN1−xSbx under conditions intended to induce phase segregation. Prior experiments with the similar alloy GaN1−xAsx, the tendency of Sb to surfact, and the low growth temperatures needed to incorporate Sb, all suggested that GaN1−xSbx alloys would likely exhibit phase segregation. We found that, except for ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…More details of the crystal growth and structural characterization will be presented elsewhere. 24 The optical properties of the films were studied by optical transmission and reflection in the spectral range of 250-2500 nm using a Perkin Elmer Lambda 950 Spectrophotometer. Figure 1 illustrates the measured absorption spectra for five of the eight GaN 1Àx Sb x thin films with compositions ranging from x ¼ 0 to 0.42.…”
mentioning
confidence: 99%
“…More details of the crystal growth and structural characterization will be presented elsewhere. 24 The optical properties of the films were studied by optical transmission and reflection in the spectral range of 250-2500 nm using a Perkin Elmer Lambda 950 Spectrophotometer. Figure 1 illustrates the measured absorption spectra for five of the eight GaN 1Àx Sb x thin films with compositions ranging from x ¼ 0 to 0.42.…”
mentioning
confidence: 99%
“…Two sets of GaN 1-x Sb x thin films are studied in this letter. The first set consists of the previously reported films 14,20 grown by multilayer intermixing at a constant temperature of 325 C with an Sb composition x up to 0.30 along 0003-6951/2016/109(25)/252102/5/$30.00…”
mentioning
confidence: 99%
“…Transmission electron microscopy (TEM) measurements performed on selected samples of the first set were reported in Ref. 20. The TEM results showed that GaN grown without Sb is polycrystalline with grains primarily consisting of 2H GaN with the (0002) planes aligned with the (0006) sapphire substrate planes.…”
mentioning
confidence: 99%